PENGARUH ATMOSFER TOKO DAN DIVERSIFIKASI PRODUK TERHADAP KEPUASAAN PELANGGAN PADA GIANT SUPERMARKET PEKANBARU - Dewi Lestari; Endang Sutrisna (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study aims to determine the influence of store atmosphere and product diversification to customer satisfaction. Where the store atmosphere and product diversification as independent variables and customer satisfaction as the dependent variable. this research is customer of Giant Supermarket Pekanbaru with sample of 100 people using Slovin formula. Sampling technique using purposive sampling technique. Data collection of research in the form of primary data by using questioner as research instrument, analysis of data used is multiple linear regression analysis using SPSS program. The result of this research is store atmosphere and diversification have positive and significant influence to customer satisfaction. Where the value of coefficient determination (R²) indicates that store atmosphere and product diversification contribute to customer satisfaction variable of 65.2%, while 34.8% is influenced by other variables not included in this study.Keywords: store atmosphere, product diversification, and customer satisfaction